The Role of Swimming in Maintaining Body Health From an Islamic Perspective - Salahudin Salahudin; Satriawan, Rabwan; Muhammad Muhammad; Furkan, Furkan (Yayasan Insan Mulia Bima, 2023)
This study aims to explore the role of swimming in maintaining a healthy body from an Islamic perspective. The research method used is a qualitative method with data collection techniques such as interviews, observation, and literature studies. The research participants consisted of swimming athletes, swimming instructors, and participants in swimming sports programs in public places who came from the Muslim community. Research results show that swimming sports can provide great benefits for body health, such as increasing muscle strength, improving the cardiovascular system, and helping to lose weight. In the view of Islam, maintaining a healthy body is a requirement that must be met by every Muslim. However, as a Muslim, it is not enough just to do swimming, but also to pay attention to aspects related to religion, such as maintaining private parts, polite behavior, and avoiding things that can interfere with worship. The conclusion from this study is that swimming can be used as a way to maintain a healthy body and fulfill religious demands. However, in doing swimming sports, it is necessary to pay attention to aspects related to religion and local culture. Therefore, the recommendation from this study is that the government or educational institutions can develop swimming sports programs that are in accordance with Islamic views and local culture. In addition, the Muslim community also needs to choose the type of sport that is in accordance with local religious and cultural views in order to maintain a healthy body and protect religion.